Political incentives and analyst bias: Evidence from China - Pittman, Jeffrey; Yang, Zhifeng; Yu, Sijia; Zhu, Haoran (Contemporary Accounting Research, 2024)
Abstract This study extends extant research on the determinants of financial analyst bias by examining the role that political incentives play. Using a series of scheduled provincial political events in China, we document that analysts are significantly more likely to issue favorable recommendations or revise their recommendations upward during political event periods, and the effect of political events on optimism is larger for analysts employed by brokerage firms affiliated with politicians. Cross‐sectional evidence suggests that the impact of political events on analyst optimism is concentrated in those provinces where capital market development is a more important performance indicator for politicians or where the incumbent politicians face a pending promotion. Stock return analyses reveal that favorable recommendations issued during political event periods are significantly less profitable in the long run and are less credible according to investor perceptions. Reinforcing our main evidence, we also find that financial analysts are more likely to issue optimistic earnings forecasts during political event periods. Collectively, our results imply that political incentives distort analyst opinions and political‐economic factors affect the corporate information environment in China.